2005
DOI: 10.1007/s10072-005-0399-4
|View full text |Cite
|
Sign up to set email alerts
|

Specific therapies for ischaemic stroke: rTPA and others

Abstract: In the last few years there have been several important advances in the understanding of cerebrovascular disorder pathophysiology that have impacted on stroke management. The development of timely and effective treatment strategies was and is still considered a high priority issue. Therapeutic options dramatically increased both in the prevention and overall in the treatment of acute ischaemic stroke (AIS). At present, whereas neuroprotection remains experimental, intravenous (i.v.) thrombolysis is the only sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Other measures include monitoring of the neurological status, adequate hydration and treatment of low blood pressure, prevention of venous thrombosis, treatment of hyperthermia, maintenance of normoglycemia, monitoring heart rhythm, removal of Foley catheter as soon as possible, treatment of pulmonary and urinary infections, and skin care to avoid decubiti [13]. At present, thrombolysis with tissue plasminogen activator or related compounds within 3 h of the onset is the most specific therapy effective in reducing mortality and disabilities associated with stroke [14, 15]. Immediate antithrombotic therapy is no longer recommended for most patients because of possible hemorrhagic complications [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Other measures include monitoring of the neurological status, adequate hydration and treatment of low blood pressure, prevention of venous thrombosis, treatment of hyperthermia, maintenance of normoglycemia, monitoring heart rhythm, removal of Foley catheter as soon as possible, treatment of pulmonary and urinary infections, and skin care to avoid decubiti [13]. At present, thrombolysis with tissue plasminogen activator or related compounds within 3 h of the onset is the most specific therapy effective in reducing mortality and disabilities associated with stroke [14, 15]. Immediate antithrombotic therapy is no longer recommended for most patients because of possible hemorrhagic complications [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, urgent routine anticoagulation with heparin, low molecular-weight heparin or heparinoid was used for AIS. However, many previous studies reported that immediate anticoagulation therapy was not associated with net short-or long-term benefit in AIS, and increased the risk of hemorrhagic complications 5,20,23) . So, this anticoagulation treatment is not recommended for most AIS patients because of increased bleeding complications, unpredictable anticoagulation effects, dependence on the adequate antithrombin level, and heparin-induced thrombocytopenia 14,15,24) .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, all stroke patients should be admitted early within the first three to six hours from ischemic symptom onset to receive the approved treatment. However, many patients with stroke are often admitted late due to several limitations such as geographic, demographic, organizational, educational, and medical factors 7,23,26) . Because most AIS patients cannot arrive at the hospital within six hours, an effective and safe treatment which can be used for AIS patients presenting beyond six hours of ischemic symptom onset was required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the thrombolytic drugs, intravenous recombinant tissue plasminogen activator (rtPA) has proved effective in reducing mortality and disability associated with ischemic stroke (Wardlaw et al, 2000). When it is administered in selected patients with acute ischemic stroke within 4.5 h of symptom onset, rtPA is highly effective in reducing death and disability (Buchan & Kennedy, 2007;Toni et al, 2005 andLansberg et al, 2009;Clark et al, 1999). Clinically, relatively few patients are treated with rtPA, primarily because the therapeutic window is prohibitively short compared to the usual delays in stroke recognition and patient transport, triaging and neuroimaging (Kwan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%